Influence of the Composition and Particle Sizes of the Fuel Mixture of Coal and Biomass on the Ignition and Combustion Characteristics; Applied Sciences; Vol. 13, iss. 19 - Glushkov D. O. Dmitry Olegovich; Zhuykov A. V. Andrey Vladimirovich; Zemlyansky N. A. Nikolay Alekseevich; Pleshko A. O. Andrey Olegovich; Fetisova O. Yu. Olga Yurjevna; Kuznetsov P. N. Petr Nikolaevich (2023, 2023)
Title screen